Investigation of Neuron Latency Modulated by Bilateral Inferior Collicular Interactions Using Whole-Cell Patch Clamp Recording in Brain Slices. (10th December 2021) - Ma, Jinzhe; Han, Yangyang; Yao, Yiting; Wang, Huimei; Chen, Mengxia; Fu, Ziying; Chen, Qicai; Tang, Jia
Abstract : As the final level of the binaural integration center in the subcortical nucleus, the inferior colliculus (IC) plays an essential role in receiving binaural information input. Previous studies have focused on how interactions between the bilateral IC affect the firing rate of IC neurons. However, little is known concerning how the interactions within the bilateral IC affect neuron latency. In this study, we explored the synaptic mechanism of the effect of bilateral IC interactions on the latency of IC neurons. We used whole-cell patch clamp recordings to assess synaptic responses in isolated brain slices of Kunming mice. The results demonstrated that the excitation-inhibition projection was the main projection between the bilateral IC. Also, the bilateral IC interactions could change the reaction latency of most neurons to different degrees. The variation in latency was related to the type of synaptic input and the relative intensity of the excitation and inhibition. Furthermore, the latency variation also was caused by the duration change of the first subthreshold depolarization firing response of the neurons. The distribution characteristics of the different types of synaptic input also differed. Excitatory-inhibitory neurons were widely distributed in the IC dorsal and central nuclei, while excitatory neurons were relatively concentrated in these two nuclei. Inhibitory neurons did not exhibit any apparent distribution trend due to the small number of assessed neurons. These results provided an experimental reference to reveal the modulatory functions of bilateral IC projections.